Approximation to the economic cost of healthcare for hypertensive patients diagnosed with COVID-19 - Calderón-Moreno, Jesús; Delgado-Rodriguez, María Jesús; Juárez-Vela, Raúl; Tejada-Garrido, Clara Isabel; de Viñaspre-Hernández, Regina Ruiz; Burgos-Esteban, Amaya; Sánchez-Conde, Pilar; Andreu-Fernández, Vicente; Gea-Caballero, Vicente; Santos-Sanchez, Jose Angel; Quintana-Diaz, Manuel; Andrés-Esteban, Eva María (Frontiers in Public Health, 2024)
Many researchers have focused their studies in Hypertension due to its over-representa5on among COVID-19 pa5ents. Both, retrospec5ve and observa5onal studies conducted close to Wuhan area have reported that hypertension is the most common comorbidity observed in pa5ents affected by COVID-19 Objec)ve: Our objec5ve is that pa5ents with arterial hypertension have a worse prognosis in terms of evolu5on leading to higher costs.We performed a retrospec5ve cross-sec5onal study. A total of 3,581 pa5ents from La Paz University Hospital (LPUH) during the period between 15 July 2020 and 31 July 2020 were included in this study Results: It should be noted that 40.71% of the pa5ents were hypertensive. As expected, hypertension was associated with males, where we observed a higher prevalence of hypertension and pa5ents with a higher age (median of 77 years (IQI: 65-85) versus 52 years (IQI: 37-64), pvalue < 0.001). hypertensive pa5ents had a higher prevalence of dyspnea (52.14% vs. 47.15%, pvalue=0.004) and altered awareness (14.89% vs. 4.30%, pvalue < 0.001). shows the non-parametric Kaplan-Meier curve where the survival of pa5ents in the two study groups is es5mated. We can see how those pa5ents with hypertension have a higher associated mortality, the difference being sta5s5cally significant, pvalue (log-rank) = 0.004. only for the appearance of complica5ons during hospitaliza5on, the group of hypertensive pa5ents reached the figure of 1,355,901.71 € compared to the total of 421,403.48 € for normotensive pa5entOur study shows the worse clinical evolu5on of pa5ents with covid in terms of associated morbidity and mortality. It also shows that the cost management of pa5ents with hypertension is greater than that of normotensive pa5ents.